Series-fed printed dipole array antenna - Wang, Heesu; Park, Ikmo (2018 11th Global Symposium on Millimeter Waves, GSMM 2018, 2018)
In this paper, we propose a high-gain series-fed eight-element printed dipole array antenna. Each dipole has the same size, the spacing between each dipole is identical, and the dipoles are connected in a series with a coplanar stripline. Broadband impedance matching is achieved with the balun, which consists of two slot lines of different lengths and widths on one side of the substrate and a tapered microstrip line on the other side of the substrate. The impedance bandwidth of the eight-element printed dipole array antenna is 34.3%, and the gain is 9.2-13.3 dBi. The radiation patterns exhibit endfire characteristics. The overall size of the designed array antenna is 15×0.254 × 47.8mm3(1.4×\0.024×4.5λ03).
Keywords: 28 GHz; Dipole arrays; End-fire antennas; Millimeter-wave antennas; Printed dipole antennas; 28 GHz; Dipole array; Endfire antenna; Millimeter-wave antenna; Printed dipole antenna